The Safety and Efficacy of Stem Cell Therapy as an Emerging Therapy for ALS: A Systematic Review of Controlled Clinical Trials - Aljabri, Ammar; Halawani, Alhussain; Bin Lajdam, Ghassan; Labban, Suhail; Alshehri, Samah; Felemban, Razaz (Frontiers in Neurology, 2021)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with a heterogeneous course that ultimately leads to death. Currently, there is no cure, and new treatments that can slow the progression of the disease are needed. Stem cell (SC) transplantation is an emerging therapy that has shown a lot of potential in recent clinical trials. This review aims to examine the results of various clinical trials on this topic, thus assessing the safety and efficacy of SC transplantation as a potential treatment for ALS. We identified 748 studies in our search, of which 134 full-text studies were assessed for eligibility. Six studies met the inclusion criteria and were included in this review. Although some of the included studies showed the positive effect of SC transplantation, other studies found there was no significant difference compared to the control group. We observed more positive effects with bone marrow mesenchymal stem cells (BM-MSC) treatments than Granulocyte colony stimulating factor (G-CSF) ones. However, other factors, such as route of administration, number of doses, and number of cells per dose, could also play a role in this discrepancy. Based on this information, we conclude that more properly conducted clinical trials are needed to appreciate the benefit of this treatment.